(untitled) (Bangladesh Journal of Urology, 2020)
We report a case in which a one and half years old baby presented with frequent loose motion 10 month back.For this her parent put her to a physician and diagnosed as a case of PUJ obastruction(left).She underwent A-H pyeloplasty in India for PUJ obstruction on Dec,16. She developed fever with chills & rigor immediately after removal of D-J stent and referred to DMCH. Open nephrostomy was done in DMCH on March,17. Antegradenephrostogram showed low lying left kidney with moderate hydronephrosis. Reexploration of left kidney was done on oct,17. Left kidney found baggy and distal ureter found atretic. Resection of distal ureter and ureteroneocystostomy with psoas hitch was done.Post operative period was uneventful. Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p.172-174